2007
DOI: 10.1521/aeap.2007.19.2.160
|View full text |Cite
|
Sign up to set email alerts
|

Social and Behavioral Determinants of Consistent Condom Use Among Female Commercial Sex Workers in Ghana

Abstract: This study investigated the social and behavioral predictors of consistent condom use among female commercial sex workers (FCSWs) in Ghana. Four hundred fifty street commercial sex workers were interviewed in Accra, Kumasi and Techiman. The level of condom education was very low (14%); however consistent condom use (all the time) with clients was relatively high (49.6%). Two hundred seventy-seven of the participants did not use condoms all the time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
49
2
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 18 publications
21
49
2
8
Order By: Relevance
“…In most sex work settings, competition for clients is intense, resulting in workers going along with each client's demands for fear of losing the client or earning less. 33,36,47,123,125,[129][130][131] Time and availability of condoms are the third and fourth themes. Sex workers have described their encounters, especially with casual partners, as brief, with minimal conversation or negotiation.…”
Section: Commercial Sexual Relationshipsmentioning
confidence: 99%
“…In most sex work settings, competition for clients is intense, resulting in workers going along with each client's demands for fear of losing the client or earning less. 33,36,47,123,125,[129][130][131] Time and availability of condoms are the third and fourth themes. Sex workers have described their encounters, especially with casual partners, as brief, with minimal conversation or negotiation.…”
Section: Commercial Sexual Relationshipsmentioning
confidence: 99%
“…We believe that educational messages to avoid risks should be passed to new as well as experienced commercial sex workers. Substantial support, such as the free distribution of condoms, is also important to encourage the adoption of safer behaviours, because the major obstacles to consistent condom use are refusal by clients, lack of availability of free condoms and lack of empowerment to negotiate with clients for safer sex (Adu-Oppong et al, 2007). In the present study, the interviewees had access to condoms, but it is likely that many others still engage in unprotected sex.…”
Section: Discussionmentioning
confidence: 83%
“…A previous study in Ghana indicated a rate of consistent condom use of 49.6% among female sex workers, even though their opportunity for condom education was only 14% (Adu-Oppong et al, 2007). In Vietnam, less than 40% of female sex workers use condoms consistently (Tuan et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In Gambia showed majority subjects were widowed or separated (69,8%) (11) Meanwhile there were 70% in Ghana and 88,8% in Swaziland female sexual workers said: single and never been married in their marital status. (10,12) Underlying reason these women became sex workers because they often did not have skills or training to be able to get alternative employment. This study found although 85,1 % had condom in their workplace and 72,3% had condom for free, but subjects who used condom in last three days when have sexual contact were less than 70%.…”
Section: Discussionmentioning
confidence: 99%
“…There are many reasons why condom not use appropriately, such as age, socioeconomic, romantic reasons, knowledge, education, marital status of clients etc. (10,11) In facts no much data about condom usage in Jayapura City. The aim of this study was to identified the condom usage behavior and also analyzed the relationship between condom usage with STI incidence among Indirect Female Sexual Worker in Jayapura City.…”
Section: Introductionmentioning
confidence: 99%